Martensitic alloy steel

The martensitic alloy steel with controlled Cr, Mo, V, W, and Nb composition addresses the challenges of high hardness and corrosion resistance, ensuring excellent toughness and wear resistance for tools and medical instruments.

JP7606234B2Active Publication Date: 2024-12-25TAKEFU TOKUSHIYU KOUZAI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022179006
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-11-08
Publication Date
2024-12-25
Estimated Expiration
2042-11-08

AI Technical Summary

Technical Problem

Conventional martensitic stainless steels face challenges in achieving high hardness, toughness, and corrosion resistance, particularly in harsh environments, leading to issues such as corrosion and wear in tools and medical instruments, and difficulty in forming sharp cutting edges.

Method used

A martensitic alloy steel composition is developed with controlled amounts of Cr, Mo, V, W, and Nb to suppress the formation of coarse carbides, maintaining a balance between hardness and corrosion resistance, featuring a specific range of these elements to ensure high hardness and toughness.

Benefits of technology

The alloy steel exhibits excellent corrosion resistance, toughness, and wear resistance, enabling the formation of sharp cutting edges and maintaining hardness even under harsh conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606234000003
    Figure 0007606234000003
  • Figure 0007606234000001
    Figure 0007606234000001
  • Figure 0007606234000002
    Figure 0007606234000002
Patent Text Reader

Abstract

To provide a martensitic alloy steel that has increased hardness while providing excellent corrosion resistance, toughness, and wear resistance.SOLUTION: A martensitic alloy steel contains, in mass%, C: 1.30-1.70%, Cr: 14.00-18.00%, Mo: 2.00-2.80%, at least one of V, W, Nb: a total of 2.10-3.60%, with the balance being Fe and inevitable impurities.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a high hardness martensitic alloy steel having excellent corrosion resistance. [Background technology]

[0002] Conventionally, martensitic stainless steels, such as SUS420J2 and SUS440C, have been used as stainless steels with a certain degree of corrosion resistance and high hardness. These martensitic stainless steels are processed into wire rods, bars, strip steel, shaped steel, forged products, etc., and are used in a wide range of applications, such as dies, blades, shafts, bearings, nozzles, valves, springs, and screws.

[0003] However, this martensitic stainless steel has the drawback of being inferior in corrosion resistance to austenitic stainless steels such as SUS304, because the hardness is ensured by increasing the C (carbon) content.

[0004] Generally, the higher the C content of stainless steel, the higher the hardness after quenching and tempering tends to be, but if the C content is increased to further increase the hardness, Cr (chromium), which forms a passive film and improves corrosion resistance, bonds with C to form Cr carbides, resulting in a side effect of reduced corrosion resistance. Therefore, in the past, other carbide-forming elements such as Mo (molybdenum), V (vanadium), and W (tungsten) were added and the amounts added were adjusted to achieve both hardness and corrosion resistance, while balancing other properties such as toughness and wear resistance (for example, Patent Documents 1 and 2 below). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2002-212679 A [Patent Document 2] Japanese Patent Application Publication No. 10-1703 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in recent years, there has been a demand for steel materials that are less susceptible to corrosion even in more severe corrosive environments and that have higher hardness, toughness, and abrasion resistance, for example, tools such as dies, medical instruments, knives, kitchen knives, hairdressing scissors, medical scalpels, and other bladed and industrial bladed tools, but there was a problem in that conventional martensitic stainless steels were not able to adequately meet such demands.

[0007] For example, during injection molding of resin molded products, the molten resin in the cylinder is pushed out by a screw and injected into a mold, but the corrosive gas generated from the molten resin can cause corrosion inside the cylinder and mold. In addition, when glass fibers or other materials are added to increase the strength of the resin, the cylinder, screw, and mold are worn out by this reinforcing material. If the wear caused by the reinforcing material and the corrosion caused by the corrosive gas occur simultaneously, the mold and other parts will be worn out more severely. Therefore, there is a demand for steel materials that are less prone to wear and corrosion even in severe corrosive environments, and have better corrosion and wear resistance, as steel materials that are used to make these molds, cylinders, screws, and other tools.

[0008] Furthermore, various treatment tools such as grasping forceps used in endoscopic examinations and surgery are composed of tiny parts and components, and the steel materials used for the components of these treatment tools must not only have excellent corrosion resistance to body fluids, but also have high hardness and toughness so that they will not break or bend during treatment, despite being tiny parts.

[0009] In recent years, there has been a demand for even better sharpness in knives, and knives with sharper cutting edges (e.g., a cutting edge angle of about 16 degrees) are being manufactured. In order to form and maintain such a sharp cutting edge, the material must have higher hardness and toughness, as well as sufficient corrosion resistance and wear resistance, but conventional martensitic stainless steels could not adequately meet these demands.

[0010] For example, as shown in Figure 1, when a blade 1 is manufactured using conventional martensitic stainless steel and this blade 1 is sharpened, if the cutting edge angle is approximately 24 degrees (Figure 1(a)), it is possible to properly form the cutting edge 11. However, if the cutting edge angle is approximately 16 degrees (Figure 1(b)), when the cutting edge 11 is sharpened against a whetstone, the cutting edge 11 will plastically deform toward the opposite side of the whetstone, making it difficult to properly form a sharp cutting edge 11.

[0011] In order to form and maintain such a sharp cutting edge, excellent mechanical properties are required, such as a cutting edge that will not chip or bend even when sharpened. To achieve this, greater base hardness and fine dispersion of metal carbides that contribute to wear resistance and do not impede sharpening of the blade are required. However, in conventional martensitic stainless steels, the balance between strengthening the base and strengthening the metal carbide dispersion was not taken into consideration, and the addition of excessive amounts of carbon and metal elements sacrificed base hardness and corrosion resistance.

[0012] The present invention has been made in consideration of the above-mentioned problems associated with conventional martensitic stainless steels, and has an object to provide a martensitic alloy steel that has higher hardness while also exhibiting excellent corrosion resistance, toughness, and wear resistance. [Means for solving the problem]

[0013] Cr is an important element that dissolves in the steel base material to improve corrosion resistance. At the same time, it also forms complex carbides (M3C, M7C3, M 23 Cr is also a carbide-forming element that contributes to improving hardness and wear resistance by forming complex carbides (C6, etc.), but the ratio of the solid solution concentration of Cr in complex carbides to the solid solution concentration in the steel matrix (distribution coefficient) tends to be larger than other carbide-forming elements such as Mo, V, and W. Conventionally, the formation of coarse complex carbides was suppressed by reducing the amount of C added, and the solid solution concentration of Cr in the matrix was ensured to maintain corrosion resistance. However, when the amount of C added is small, the matrix is ​​not solid solution strengthened by quenching heat treatment, and high hardness cannot be obtained.

[0014] The inventors therefore focused on the carbide formation tendency of added elements such as Cr, Mo, V, W, and Nb (niobium), and came up with the idea of ​​suppressing the formation of coarse complex carbides by adjusting the added amounts of V, W, and Nb, which have a relatively high carbide formation tendency. They also discovered that it was necessary to improve not only the hardness of the steel as a whole containing these carbides, but also the hardness of the steel base material itself. As a result of extensive research, they have completed the present invention.

[0015] That is, the martensitic alloy steel according to the present invention contains, in mass%, C: 1.30 to 1.70%; Si:0.19~0.34%, Mn:0.10~0.31%, It is characterized by a composition consisting of Cr: 14.00-18.00%, Mo: 2.00-2.80%, one or more of V, W and Nb: 2.10-3.60% in total, and the remainder being Fe and unavoidable impurities.

[0016] The martensitic alloy steel according to the present invention is characterized in that it satisfies the relationship: -1.2%≦Mo%-(V+W+Nb)%≦-0.2%.

[0017] Moreover, the martensitic alloy steel according to the present invention is characterized in that V: 1.50 to 2.10%, W: 0.50 to 1.40%, and Nb: 0.20 to 0.60%. Effect of the Invention

[0018] The martensitic alloy steel according to the present invention contains predetermined amounts of V, W, and Nb, which have a relatively high tendency to form carbides, and therefore effectively suppresses the formation of complex carbides that reduce corrosion resistance while at the same time ensuring the hardness of the steel base material itself, thereby exhibiting excellent corrosion resistance, toughness, and wear resistance while maintaining high hardness. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is an enlarged schematic cross-sectional view of the cutting edge of a blade made from conventional martensitic stainless steel, with (a) a cutting edge angle of 24 degrees and (b) a cutting edge angle of 16 degrees. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, an embodiment of the martensitic alloy steel according to the present invention will be described. First, the reasons for limiting the components constituting the martensitic alloy steel according to the present invention will be described.

[0021] C (carbon): 1.30~1.70% Carbon (C) is an element that dissolves in the steel base material to increase hardness, and also combines with Cr, Mo, V, W, and Nb to form high-hardness carbides to further increase hardness. If C falls below 1.30%, the hardness of the steel base material cannot be ensured. On the other hand, if it exceeds 1.70%, the amount of carbides becomes excessively large, and toughness decreases, and the amount of Cr, Mo, etc. dissolved in the base material becomes insufficient, decreasing corrosion resistance.

[0022] Cr (chromium): 14.00-18.00% Cr (chromium) is an element that dissolves in the steel base material to form a passive film to improve corrosion resistance, and also forms carbides to improve hardness and wear resistance. If the Cr content is less than 14.00%, the corrosion resistance required for cutlery such as knives and kitchen knives cannot be ensured, and if it exceeds 18.00%, the amount of carbides becomes excessively large, reducing toughness.

[0023] Mo (molybdenum): 2.00-2.80% Mo (molybdenum) is an element that forms a stable passive film together with Cr to improve corrosion resistance, and also forms harder carbides to improve hardness and wear resistance. If Mo is less than 2.00%, the necessary corrosion resistance, hardness, and wear resistance cannot be ensured, and secondary hardening by tempering cannot be obtained sufficiently. On the other hand, if it exceeds 2.80%, the amount of carbides becomes excessively large, and toughness decreases.

[0024] V (vanadium): 1.50-2.10% Vanadium (V) is an element that forms hard carbides to improve hardness and wear resistance, and refines crystal grains to improve toughness. If V is less than 1.50%, the necessary hardness and wear resistance cannot be ensured, and if it exceeds 2.10%, the amount of carbides becomes excessively large, reducing toughness and worsening workability during plastic processing.

[0025] W (tungsten): 0.50 to 1.40% W (tungsten) is an element that forms hard carbides to improve hardness and wear resistance, and refines crystal grains to improve toughness. If W is less than 0.50%, the necessary hardness and wear resistance cannot be ensured, and if it exceeds 1.40%, the amount of carbides becomes excessively large, reducing toughness and worsening workability during plastic processing.

[0026] Nb (niobium): 0.20 to 0.60% Nb (niobium) is an element that forms hard carbides to improve hardness and wear resistance, and refines crystal grains to improve toughness. If the Nb content is less than 0.20%, the necessary hardness and wear resistance cannot be secured, and if it exceeds 0.60%, an excessive amount of Nb carbide is generated, reducing the amount of C required for matrix solid solution strengthening, and reducing the matrix solid solution strengthening ability.

[0027] One or more of V, W, and Nb: 2.10 to 3.60% in total V, W, and Nb are elements with a higher tendency to form carbides than Cr, and the formation of carbides by these elements can suppress the formation of Cr carbides, preventing a shortage of Cr in the base material and ensuring the necessary corrosion resistance. In particular, Nb has a higher tendency to form carbides than other elements, so it can more effectively suppress the formation of Cr carbides and improve corrosion resistance. If the total of one or more of V, W, and Nb is below 2.10%, the formation of Cr carbides cannot be effectively suppressed, and corrosion resistance decreases. On the other hand, if it exceeds 3.60%, the amount of carbides becomes excessively large, the amount of solute C during quenching decreases, and the hardness of the steel base material decreases.

[0028] -1.2%≦Mo%-(V+W+Nb)%≦-0.2% Mo, like V, W, and Nb, is an element that forms hard carbides to improve hardness and wear resistance, and also forms a stable passive film together with Cr to improve corrosion resistance. If the difference between the amount of Mo added and the total amount of V, W, and Nb added is within the range of -1.2% to -0.2%, better corrosion resistance and higher hardness are exhibited.

[0029] In addition, the martensitic alloy steel according to the present invention does not intentionally add Co (cobalt), which dissolves in the steel matrix and promotes matrix strengthening, except for the inevitable impurity. This is because the martensitic alloy steel according to the present invention can ensure the necessary matrix strengthening ability by suppressing the formation of Cr carbides by adding predetermined amounts of V, W, and Nb as described above. Therefore, the martensitic alloy steel according to the present invention does not substantially contain Co, which is designated as a conflict mineral, and thus realizes a sustainable composition design.

[0030] The martensitic alloy steel according to the present invention can be produced by a powder metallurgy method in addition to the conventional melting method. The martensitic alloy steel produced by the powder metallurgy method can have fine crystal grains and a large amount of carbides uniformly and finely distributed, so that it can achieve both high levels of hardness and toughness. EXAMPLES

[0031] Examples 1 to 8 and Comparative Examples 1 to 10 having the compositions shown in Table 1 were manufactured, and tests were carried out on each steel type regarding hardness, bending strength (toughness), wear resistance, cutting performance as a blade, and corrosion resistance. The results are shown in Table 2.

[0032] For each steel type, test pieces were taken from the steels processed to a thickness of 2 mm and quenched and tempered. The quenching and tempering temperatures were set to the temperature at which the maximum hardness of each steel type was obtained. Comparative Examples 9 and 10 (SUS440C) were manufactured by the melting method, while the others were manufactured by the powder metallurgy method.

[0033] [Table 1]

[0034] [Table 2]

[0035] "hardness" The hardness was measured on the polished surface of the test piece using a Vickers hardness tester (load 500 grams).

[0036] "Bending strength" A test piece adjusted to 2 mm x 50 mm was held at one end by a jig, and the strength at the time of break was measured.

[0037] "Wear resistance" Three test pieces (total area 1050 mm2) adjusted to 5 mm x 70 mm were polished for 15 minutes with a polishing machine at a rotation speed of 200 rpm and a load of approximately 200 N, using emery paper (#80) as the mating material, and the total weight loss (amount of wear) of the test pieces was then measured. The less the amount of wear, the better the wear resistance.

[0038] "Cutting performance" Two types of blades (cutting edge angle 16±1 degree and cutting edge angle 24±1 degree) were made under the same conditions, and these two types of blades were fixed to a sharpness testing machine. A large number of sheets of 7.5 mm wide paper equivalent to newspaper were stacked and a load of approximately 750 grams was applied, while the blades were moved back and forth over a distance of 20 mm, and the number of sheets of paper cut was measured.

[0039] "Corrosion resistance" A test piece adjusted to 18 mm x 18 mm was embedded in epoxy resin, and the end surface was polished with a roughness of 1000. A salt spray test was performed under the condition of continuous spraying of 5% NaCl aqueous solution at 35°C and 75 kPa for 24 hours. After the test, the depth of each pitting corrosion that occurred in an area of ​​14 mm x 14 mm excluding the ridge of the polished surface of the test piece was measured. The smaller the maximum pitting corrosion depth of each test piece, the less the amount of polishing required during polishing and regeneration can be performed, and the regeneration work can be easily performed. In addition, the conventionally used pitting corrosion index (PRE value = Cr% + 3.3Mo% + 16N%) is shown in Table 2 for each steel type of Examples 1 to 8 and Comparative Examples 1 to 10. This PRE value is an index that predicts corrosion resistance from the components of steel, but the test results in these Examples and Comparative Examples overturn the prediction based on this PRE value.

[0040] As shown in Tables 1 and 2, in Examples 1 to 8 according to the present invention, the total amount of V, W, and Nb, which are elements that have a higher tendency to form carbides than Cr, is in the range of 2.10 to 3.60%, so that the formation of complex carbides can be effectively suppressed, and excellent corrosion resistance can be exhibited while ensuring the hardness of the steel base material itself. When a blade is made, it also shows excellent cutting performance. In addition, since various carbides are not excessively formed, it shows appropriate toughness and wear resistance. Usually, toughness is sacrificed when hardness is increased, but in Examples 1 to 8, both are achieved.

[0041] In particular, in Examples 2 to 5 and 8, the difference between the amount of Mo added and the total amount of V, W, and Nb added is in the range of -1.2% to -0.2%, so that they exhibit higher hardness and a better balance in corrosion resistance, toughness, and wear resistance.

[0042] In contrast, in Comparative Example 1, the total amount of V, W, and Nb added is within the range of the present invention, but the amount of Cr added is below the range of the present invention. Therefore, although the material exhibits high hardness, the maximum pitting depth and the total pitting depth are larger than those of Examples 1 to 8, and the corrosion resistance is inferior.

[0043] In addition, in Comparative Example 2, the total amount of V, W, and Nb added is within the range of the present invention, but the amount of C added is below the range of the present invention, so that although Comparative Example 2 shows high corrosion resistance, it is inferior in hardness and cutting performance as a blade compared to Examples 1 to 8. In particular, in Comparative Example 2, although the Vickers hardness of the entire steel containing various carbides is about the same as that of Comparative Example 10 (SUS440C), the hardness of the steel base itself is insufficient due to the decrease in the amount of solid-solubilized C in the steel base, so that when the blade is manufactured, although it is possible to form a cutting edge with a cutter angle of 24±1 degrees, it is difficult to properly form a sharper cutting edge with a cutter angle of 16±1 degrees, and the cutting performance at a cutter angle of 16±1 degrees is significantly inferior, with the number of cuts being 0.

[0044] Furthermore, in Comparative Example 6, the total amount of V, W, and Nb added is within the range of the present invention, but the amount of Mo added is below the range of the present invention, so that the hardness is inferior to Examples 1-8.

[0045] In Comparative Examples 3 and 4, although the amounts of C and Cr added are significantly higher than the range of the present invention, the total amount of V, W, and Nb added is lower than the range of the present invention. As a result, the Cr carbide suppression effect is not sufficient, and the corrosion resistance is significantly inferior to Examples 1 to 8, resulting in general corrosion.

[0046] In addition, in Comparative Examples 7, 9, and 10, the total amount of V, W, and Nb added is below the range of the present invention, so the Cr carbide suppression effect is not sufficient, and the corrosion resistance is inferior to Examples 1 to 8. In particular, although Comparative Example 7 exhibits a high pitting corrosion index (PRE value) of 26.2, the maximum pitting corrosion depth and total pitting corrosion depth are larger than those of Examples 1 to 8, and the corrosion resistance is inferior.

[0047] Comparative Example 5, in which the total amount of V, W, and Nb added exceeds the range of the present invention, exhibits high corrosion resistance, but has poorer hardness than Examples 1 to 8. In Comparative Example 5, the amount of carbides is excessively large, so that although the Vickers hardness of the entire steel containing various carbides is similar to that of Comparative Example 10 (SUS440C), the hardness of the steel base itself is insufficient due to the reduced amount of dissolved C in the steel base, and therefore, when a blade is manufactured, the cutting performance when the cutting edge angle is 16±1 degree is inferior to that when the cutting edge angle is 24±1 degree.

[0048] In addition, in Comparative Example 8, the total amount of V, W, and Nb added exceeds the range of the present invention, and therefore the hardness is inferior to Examples 1 to 8, even though the amounts of C and Cr added exceed the range of the present invention.

[0049] As is clear from these test results, according to the present invention, by utilizing the relatively high carbide formation tendency of V, W, and Nb, it is possible to suppress the formation of complex carbides that reduce corrosion resistance and ensure the necessary corrosion resistance, while at the same time ensuring the hardness of the steel base material itself, thereby providing a martensitic alloy steel that is harder yet also has excellent corrosion resistance, toughness, and wear resistance. [Explanation of symbols]

[0050] 1. Knives 11 Cutting Edge

Claims

1. A martensitic alloy steel characterized by having a composition consisting of, in mass%, 1.30 to 1.70% C, 0.19 to 0.34% Si, 0.10 to 0.31% Mn, 14.00 to 18.00% Cr, 2.00 to 2.80% Mo, 2.10 to 3.60% in total of one or more of V, W and Nb, with the remainder being Fe and unavoidable impurities.

2. 2. The martensitic alloy steel according to claim 1, wherein the relationship is -1.2%≦Mo%-(V+W+Nb)%≦-0.2%.

3. 3. The martensitic alloy steel according to claim 1, wherein V is 1.50 to 2.10%, W is 0.50 to 1.40%, and Nb is 0.20 to 0.60%.

Citation Information

Patent Citations

  • Alloy steel for cutting tool, excellent in corrosion resistance and cutting quality

    JP1998001703A

  • Plug mill plug for manufacturing seamless steel tube

    JP1999197716A

  • EDGE TOOL AND Fe-BASED ALLOY FOR EDGE TOOL USED THEREFOR

    JP2002212679A

  • Sintered sliding member and working implement-connecting apparatus

    JP2012041639A